2022
DOI: 10.3389/fphys.2022.849603
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Disturbance and Morphological Alterations Following the Right Atrial Ligation in the Chick Embryo

Abstract: Collectively known as congenital heart defects (CHDs), cardiac abnormalities at birth are the most common forms of neonatal defects. Being principally responsible for the heart‘s pumping power, ventricles are particularly affected by developmental abnormalities, such as flow disturbances or genomic defects. Hypoplastic Right Heart Syndrome (HRHS) is a rare disease where the right ventricle is underdeveloped. In this study, we introduce a surgical procedure performed on chick embryo, termed right atrial ligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…51,60 For example, recently, we demonstrated that surgical interference (left atrial ligation) affected hemodynamics and induced clinically relevant cardiac disease morphologies. 62 In a following study, we introduced a new surgical approach called right atrial ligation to study the influence of right-side flow disturbance in chick embryo heart development 15.…”
Section: Doppler Echocardiography For Measuring Flow Velocities In Ch...mentioning
confidence: 99%
See 2 more Smart Citations
“…51,60 For example, recently, we demonstrated that surgical interference (left atrial ligation) affected hemodynamics and induced clinically relevant cardiac disease morphologies. 62 In a following study, we introduced a new surgical approach called right atrial ligation to study the influence of right-side flow disturbance in chick embryo heart development 15.…”
Section: Doppler Echocardiography For Measuring Flow Velocities In Ch...mentioning
confidence: 99%
“…Thus, the chick embryo's heart and vasculature are visible and accessible for experimentation by removing a small piece of eggshell (Figure 1). Due to these attributes and the accessibility of chicken eggs, it is not surprising that the chick embryo has become established as a premier developmental animal model for studying cardiovascular physiology 14 and an excellent platform to explore the influences of hemodynamic forces within the cardiovascular system 15‐17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating blood flow is therefore important to understanding heart development, but current capabilities in studying early mammalian blood flow patterns are limited. Aspects of biomechanical regulation of cardiac development have been studied in a number of species and by computational models [6,7]. Toward investigation of the biomechanical factors regulating cardiac development in mouse models of human diseases, recent research has established optical coherence tomography (OCT) imaging of mouse embryonic cardiodynamics [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For a deeper understanding of the cilia-driven flow, it is necessary to numerically model the problem and solve the physically governing fluid flow equations during the movement of the cilia. Computational fluid dynamics (CFD) is an important modality for investigating the biological flows in the human body which cannot be directly analyzed using experimental visualization techniques, such as in cilia-driven flow [ 62 , 63 ]. The complex flow geometries can be extracted with the use of image-processing techniques [ 64 ].…”
Section: Introductionmentioning
confidence: 99%